BENDING TRIANGULAR FINITE ELEMENT WITH A FICTITIOUS FOURTH NODE BASED ON THE STRAIN APPROACH - Himeur, Mohamed; Guenfoud, Mohamed (Courrier du Savoir, 2014)
We present a new plate bending triangular finite element. It is developed in perspective to building shell elements. Its formulation uses concepts related to the deformation approach, the fourth fictitious node, the static condensation and analytic integration. It is based on the assumptions of the theory of thin plates (Kirchhoff theory). The approach has resulted in a bending plate finite element (HIMEUR) competitive, robust and efficient.